1994
DOI: 10.1104/pp.104.1.201
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Analysis of Chloroplast Division and Expansion in Arabidopsis thaliana

Abstract: A nuclear recessive mutant of Arabidopsis thaliana, arc5, has been isolated in which there is no significant increase in chloroplast number during leaf mesophyll cell expansion and in which there are only 13 chloroplasts per mesophyll cell compared with 121 in wild-type cells. Mature arc5 chloroplasts in fully expanded mesophyll cells are 6-fold larger than in wild-type cells. A large proportion of arc5 chloroplasts also show some degree of central constriction, suggesting that the mutation has prevented the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
162
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(178 citation statements)
references
References 16 publications
15
162
0
1
Order By: Relevance
“…Like other chloroplast division mutants, leaf mesophyll cells in arc5 (Ler) mutants contain fewer and larger chloroplasts than do wild type cells, which have about 120 chloroplasts at maturity (21,22) (Fig. 1 A).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Like other chloroplast division mutants, leaf mesophyll cells in arc5 (Ler) mutants contain fewer and larger chloroplasts than do wild type cells, which have about 120 chloroplasts at maturity (21,22) (Fig. 1 A).…”
Section: Resultsmentioning
confidence: 97%
“…Arabidopsis thaliana strains Columbia (Col-0) and Landsberg erecta (Ler) were used for all experiments as indicated. The arc5 mutant was identified in the Ler background by Pyke and Leech (21). Plants were grown as described (4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 3 and 9 h, agb1-2 plants showed large patches of weakly fluorescing epidermal cells. Chloroplast fluorescence in epidermal cells, which have fewer but larger chloroplasts than guard cells in Arabidopsis (Pyke and Leech, 1994), was more intense in the agb1-2 mutant than in wild-type plants. At 20 h after the onset of O 3 exposure, the cellular distribution of ROS fluorescence in agb1-2 plants resembled that in wild-type plants and often was more intense.…”
Section: The Early Component Of the Oxidative Burst Requires Both Ga mentioning
confidence: 94%
“…A number of genes have been identified that promote or restrain chloroplast division (for review, see Osteryoung and Pyke, 2014). One early discovery for the arc (accumulation and replication of chloroplast) mutants was that their chloroplast coverage did not diverge from the wild type, indicating that the mechanisms that regulate chloroplast size and division are independent (Pyke and Leech, 1994). One protein recently identified as a regulator of chloroplast coverage is REDUCED CHLOROPLAST COVERAGE1, which is extraplastidic in localization (Larkin et al, 2016).…”
Section: Regulation Of Chloroplast Number and Sizementioning
confidence: 99%